A new dirivultid copepod (Siphonostomatoida) from hydrothermal vent fields of the Izu-Bonin Arc in the North Pacific Ocean - Uyeno, Daisuke; Watanabe, Hiromi K; Shimanaga, Motohiro (Zootaxa, 2018)
A new species of dirivultid copepod (Siphonostomatoida) is described from hydrothermal vents in a volcanic seamount in Izu-Bonin Arc, western part of North Pacific Ocean. The copepod was collected during the research cruise NT13-09 using the R/V Natsushima with the ROV Hyper-Dolphin in April 2013. The type series of the new species was collected from the populations of Paralvinella spp. (Annelida: Alvinellidae) on an active vent chimney at the depth of 795 m. Stygiopontius senokuchiae n. sp. is most closely related to S. teres Humes, 1996 but clearly distinguished from the latter species by the possession of the following characters: the basis of leg 1 with an attenuated inner process; the genital double somite with a conical process lateral to the genital opening; and caudal rami without distal process. The findings of the copepod in the present study represents the first record of nominal species of the Dirivultidae from Japanese waters and a record of the shallowest depth of the genus. A key to species of the genus Stygiopontius from Western Pacific is provided.